2021
DOI: 10.2147/rmhp.s292354
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice About Coronavirus Disease (COVID-19) Pandemic and Its Psychological Impact on Students and Their Studies: A Cross-Sectional Study Among Pharmacy Students in Saudi Arabia

Abstract: Background Individuals’ knowledge, attitude and practice towards preventive and precautionary measures of COVID-19 are essential to control the spread of the disease. Consequently, the aims of the study were to evaluate knowledge, attitude and practice of pharmacy students towards the pandemic and to assess its psychological impact on them to provide future guidance. Methods A cross-sectional, questionnaire-based study was conducted via a web-based survey in May 2020. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 101 publications
15
46
1
Order By: Relevance
“…Similarly, Indonesian females were also reported avoiding prayers, physical gatherings and take preventive measures at worship places during the COVID-19 pandemic than males [24]. In general, our results are also consistent with recent studies conducted in Saudi Arabia which reported that younger and women have higher optimistic attitudes towards the COVID-19 pandemic than men [13,14,[25][26][27]. These results can be attributed to the increased usage of the social media channels by younger, females, job seekers as well as housewives, which can improve the Islamic knowledge and attitudes regarding the disease, compared to their counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, Indonesian females were also reported avoiding prayers, physical gatherings and take preventive measures at worship places during the COVID-19 pandemic than males [24]. In general, our results are also consistent with recent studies conducted in Saudi Arabia which reported that younger and women have higher optimistic attitudes towards the COVID-19 pandemic than men [13,14,[25][26][27]. These results can be attributed to the increased usage of the social media channels by younger, females, job seekers as well as housewives, which can improve the Islamic knowledge and attitudes regarding the disease, compared to their counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…us, social distancing would not be effective; screening and surveillance were expanded to try to detect potential outbreaks before they could ignite [17]. Protective measures include hand washing or using an alcoholbased rub frequently and not touching the face [25]. e COVID-19 pandemic has raised a dilemma between economic stimulation and public health control [26].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the above findings and recommendations, this study is not without limitations. The construction of our dependent variable is based on a well-known study (10) but is also different from the variables used in other studies (39,40). Therefore, the difference in the type of measure used may have an impact on assessing the inequality for the variable.…”
Section: Discussionmentioning
confidence: 99%